Effect of Workplace Stretching Exercise (WSE) Intervention on Musculoskeletal Disorders (MSDS) Complaints - Litza Prihanto, Ratna; Widajati, Noeroel; Aderilla, Savira (Syntax Corporation, 2025)
Musculoskeletal Disorders (MSDs) referred to complaints affecting the muscles and bones, ranging from sprains to chronic disorders that carried a risk of disability. Proper ergonomic implementation supported workers' health, comfort, and productivity, while poor ergonomics could trigger complaints. Identifying work positions, processes, and layouts was necessary to prevent MSDs. This study analyzed the effect of Workplace Stretching Exercise (WSE) on MSDs complaints among building construction project workers in Malang Regency. This study employed a quantitative approach with a Quasi-Experimental design and the Pretest-Posttest Control Group method. The study results indicated differences in MSDs complaints before and after the WSE intervention, demonstrating the effectiveness of the intervention. Ordinal regression analysis showed that several factors had a significant effect on MSDs complaints, including age 17-25 years (ρ=0.016), age 26-35 years (ρ=0.004), very low work posture (ρ=0.006), low work posture (ρ=0.008), work duration (ρ=0.007), low workload (ρ=0.023), moderate workload (ρ=0.015), and the WSE intervention (ρ=0.020). These findings indicated that, in addition to individual and work-related factors, the implementation of WSE played a role in reducing MSDs complaints among building construction project workers in Malang Regency. The researchers recommended that workers maintain optimal body posture, apply safe lifting techniques, avoid prolonged static positions, and perform regular stretching exercises as a preventive measure against musculoskeletal injuries